Negative electrode material for secondary battery, and secondary battery

By using composite particles containing silicon and S-containing conductive layer in the negative electrode material of the secondary battery, the problem of lithium silicate being eroded by decomposition in the non-aqueous electrolyte secondary battery is solved, and side reactions are suppressed and charging is improved. Effects of discharge cycle characteristics.

CN119452482APending Publication Date: 2025-02-14PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD

Patent Information

Application Number
CN202380049972.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Lithium silicate is easily eroded by decomposition in non-aqueous electrolyte secondary batteries, resulting in an increase in surface area and intensified side reactions, which in turn leads to a decrease in charge and discharge cycle characteristics.

Method used

A negative electrode material containing silicon-containing material is used, which includes composite particles containing silicon and a conductive layer disposed on the surface of composite particles. The conductive layer contains sulfur components and the content of sulfur elements is less than 50 mass %.

Benefits of technology

By covering the surface of the composite particles with S-containing conductive layer, cracks and cracks of the composite particles are suppressed, the influence of the electrolyte is slowed down, and side reactions are suppressed, and the charge and discharge cycle characteristics are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119452482A_ABST
    Figure CN119452482A_ABST
Patent Text Reader

Abstract

This negative electrode material for a secondary battery contains a silicon-containing material provided with composite particles containing silicon and a conductive layer disposed on the surfaces of the composite particles. The composite particles include an ion conducting phase and a silicon phase dispersed within the ion conducting phase. The conductive layer contains a sulfur component, and the content N1 of elemental sulfur in the conductive layer is 50 mass% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a negative electrode material for a secondary battery and a secondary battery using the negative electrode material for a secondary battery. Background Art

[0002] In recent years, non-aqueous electrolyte secondary batteries have high voltage and high energy density, and therefore can be expected to be used as power sources for small civilian applications, power storage devices, and electric vehicles. In the pursuit of high energy density of secondary batteries, the use of materials containing silicon (silicone) that can alloy with lithium as negative electrode active materials with high theoretical capacity density is expected.

[0003] Patent Document 1 proposes a negative electrode active material having a Li 2z SiO 2+z A lithium silicate phase represented by (0<z<2), and silicon particles dispersed in the lithium silicate phase.

[0004] Patent document 2 proposes a lithium ion battery, which is a lithium ion battery including a negative electrode and an electrolyte, wherein the negative electrode includes composite particles, the composite particles include silicon-based domains, the composite particles include a matrix material in which the silicon-based domains are embedded, the composite particles have an interface with the electrolyte, an SEI layer exists at the interface, and the SEI layer includes one or more compounds having a carbon-carbon chemical bond and one or more compounds having a carbon-oxygen chemical bond. In the X-ray photoelectron spectroscopy measurement of SEI, the ratio defined by dividing the area of ​​the first peak derived from the CC chemical bond having a center at 284.33 eV by the area of ​​the second peak derived from the CO chemical bond having a center at 285.83 eV is at least 1.30.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2016 / 35290 Pamphlet

[0008] Patent Document 2: Japanese Patent Application No. 2020-537335 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] The negative electrode active material having a lithium silicate phase and silicon particles dispersed therein of Patent Document 1 is promising. However, lithium silicate is easily corroded by decomposition products (such as HF) generated in the side reactions of the non-aqueous electrolyte components. If the lithium silicate is corroded, the surface area of ​​the lithium silicate phase increases and the side reactions are promoted. As a result, the capacity of the non-aqueous electrolyte secondary battery deteriorates with repeated charge and discharge cycles.

[0011] Solutions for solving problems

[0012] In view of the above, one aspect of the present disclosure relates to a negative electrode material for a secondary battery, comprising a silicon-containing material, wherein the silicon-containing material comprises composite particles containing silicon and a conductive layer disposed on the surface of the composite particles, wherein the composite particles comprise an ion conductive phase and a silicon phase dispersed in the ion conductive phase, wherein the conductive layer comprises a sulfur component, and the content rate N of the sulfur element in the conductive layer is 1 It is 50 mass % or less.

[0013] Another aspect of the present disclosure relates to a secondary battery including a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode includes a carbon material and the negative electrode material for a secondary battery.

[0014] Effects of the Invention

[0015] According to the present disclosure, the degradation of the capacity of the secondary battery accompanying the repetition of the charge and discharge cycle is suppressed. Hereinafter, such degradation of the capacity is also referred to as "deterioration of the charge and discharge cycle characteristics".

[0016] The novel features of the present invention are recorded in the attached claims, but the present invention relates to both structure and content. Other objects and features of the present invention will be further understood through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 1 is a diagram schematically showing a cross section of a composite particle (silicon-containing material) covered with an S-containing conductive layer according to one embodiment of the present disclosure.

[0018] Figure 2 This is a diagram schematically showing a cross section of a composite particle (silicon-containing material) covered with a S-containing conductive layer after several cycles of charge and discharge.

[0019] Figure 3 This is a schematic perspective view showing a partially cutaway portion of a secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0020] Hereinafter, the embodiments of the present disclosure will be illustrated, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values, materials, etc. may be illustrated, but other numerical values, materials, etc. may also be applied as long as the effects of the present invention can be obtained. It should be noted that known constituent elements may also be applied to constituent elements other than the characteristic parts of the present disclosure. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, and may replace "numerical value A or more and numerical value B or less". In the following description, when the lower limit and upper limit of numerical values ​​related to specific physical properties, conditions, etc. are illustrated, as long as the lower limit does not become above the upper limit, any of the illustrated lower limits may be arbitrarily combined with any of the illustrated upper limits. When multiple materials are illustrated, one may be selected and used alone, or two or more may be combined and used.

[0021] In addition, the present disclosure includes a combination of matters recorded in two or more claims selected arbitrarily from the plurality of claims recorded in the attached claims. That is, as long as no technical contradiction occurs, a combination of matters recorded in two or more claims may be selected arbitrarily from the plurality of claims recorded in the attached claims.

[0022] (Negative electrode materials for secondary batteries)

[0023] The negative electrode material for a secondary battery according to an embodiment of the present disclosure includes a silicon-containing material.

[0024] [Silicon-containing materials]

[0025] The silicon-containing material comprises composite particles containing silicon and a conductive layer disposed on the surface of the composite particles. The composite particles include an ion conductive phase and a silicon phase dispersed in the ion conductive phase. The conductive layer includes a sulfur (S) component, and the content of sulfur in the conductive layer is N 1 It is 2 mass % or less.

[0026] Hereinafter, the conductive layer containing the S component is also referred to as an “S-containing conductive layer.” In addition, the negative electrode material comprising the composite particles and the conductive layer disposed on the surface thereof, wherein the conductive layer contains the S component, is also referred to as a “composite particle having an S-containing conductive layer.”

[0027] It should be noted that the state in which the S-containing conductive layer is arranged on the surface of the composite particle includes the state in which the S-containing conductive layer is attached or precipitated on at least a portion of the surface of the composite particle, or the state in which the S-containing conductive layer covers at least a portion of the surface of the composite particle in a film form.

[0028] The silicon phase repeatedly expands and contracts as the nonaqueous electrolyte secondary battery is charged and discharged, but the silicon phase is dispersed in the ion conductive phase, so the composite particles have excellent structural stability.

[0029] By covering the surface of the composite particles with a conductive layer, cracks and fissures of the composite particles are suppressed, and the composite particles are protected from the influence of the electrolyte, so that side reactions are suppressed. Thus, the corrosion of the matrix (ion conductive phase) caused by the side reaction with the electrolyte is suppressed, and the charge-discharge cycle characteristics are improved. Further, by making the conductive layer contain S components, the charge-discharge cycle characteristics are significantly improved.

[0030] In addition, by covering the surface of the composite particles with a S-containing conductive layer, the conductivity of the composite particles can be greatly improved. The S-containing conductive layer preferably contains a carbon material as a main component. The carbon material preferably contains at least one selected from the group consisting of a carbon compound and a carbonaceous material. The carbonaceous material can be crystalline carbon or amorphous carbon.

[0031] The reactivity of the decomposition products such as HF generated by the S component in the S-containing conductive layer and the components of the electrolyte or the side reactions of the electrolyte components (hereinafter referred to as electrolyte decomposition products) is high, and through the reaction, a film (solid electrolyte film) containing S can be formed in a manner covering the conductive layer or composite particles. The film containing S is firm and stable. By forming a firm and stable film, the contact opportunity between the electrolyte decomposition product and the ion-conducting phase is significantly reduced. Therefore, the increase in the surface area of ​​the ion-conducting phase caused by corrosion is suppressed, and the reduction in the charge and discharge cycle characteristics caused by the progress of the side reaction is suppressed.

[0032] The content N of sulfur element in the S-containing conductive layer 1 50 mass % or less. 1 It may be 30% by mass or less, or 25% by mass or less. 1 The content may be 1% by mass or more and 30% by mass or less, or 1% by mass or more and 25% by mass or less.

[0033] The ratio N of the mass of sulfur contained in the S-containing conductive layer to the mass of the silicon-containing material obtained by adding up the mass of the S-containing conductive layer and the composite particles is 2 It can be 0.02% or more (0.0002 or more). 2 It can be 0.02% or more and 1% or less (0.0002 or more and 0.01 or less). 2 In this range, the effect of suppressing the reduction in charge and discharge cycle characteristics is high.

[0034] The content of sulfur element contained in the S-containing conductive layer can be determined by a carbon / sulfur analyzer described later.

[0035] Sulfur compounds may also be contained in the electrolyte (electrolyte) of the secondary battery. The sulfur compounds contained in the electrolyte are decomposed on the surface of the silicon-containing material, and a coating (solid electrolyte coating) containing S can be formed in a manner that covers the conductive layer or composite particles. As a result, the increase in the surface area of ​​the ion-conducting phase caused by dissolution can be suppressed, and the reduction in the charge and discharge cycle characteristics caused by the conduction of side reactions can be suppressed. However, when sulfur compounds are contained in the electrolyte at a high concentration, the battery case is easily corroded. In contrast, by making the conductive layer contain S components, the corrosion of the battery case can be suppressed, and a solid electrolyte coating containing S can be efficiently formed on the surface of the silicon-containing material.

[0036] The average particle size of the composite particles is, for example, not less than 1 μm and not more than 25 μm, or not less than 4 μm and not more than 15 μm. Within the above particle size range, it is easy to alleviate the stress caused by the volume change of the composite particles accompanying charge and discharge, and it is easy to obtain good cycle characteristics. The surface area of ​​the composite particles is also of appropriate size, and the capacity reduction caused by the side reaction with the non-aqueous electrolyte is also suppressed. The average particle size of the composite particles refers to the particle size (volume average particle size) at which the volume cumulative value becomes 50% in the particle size distribution measured by the laser diffraction scattering method. As a measuring device, for example, "LA-750" manufactured by HORIBA Co., Ltd. (HORIBA) can be used. The S-containing conductive layer does not substantially affect the average particle size of the composite particles, so the average particle size of the composite particles and the average particle size of the composite particles having the S-containing conductive layer can also be regarded as equivalent.

[0037] The average particle size of the composite particles can also be measured by observing the cross section of the negative electrode active material layer of the negative electrode taken out by disassembling the secondary battery using SEM or TEM. In this case, the average particle size is obtained by taking the arithmetic average of the maximum diameters of any 100 particles.

[0038] Silicon-containing materials and composite particles can be removed from the battery by the following method. First, the battery in a fully discharged state is disassembled to remove the negative electrode, and the negative electrode is washed with anhydrous methyl ethyl carbonate or dimethyl carbonate to remove the non-aqueous electrolyte component. As described later, the negative electrode has a negative electrode collector and a negative electrode mixture layer supported on its surface. Therefore, the negative electrode mixture layer is peeled off from the copper foil and crushed with a mortar to obtain a sample powder. Then, the sample powder is dried in a dry atmosphere for 1 hour and immersed in lightly boiled 6M hydrochloric acid for 10 minutes to remove elements other than silicon-containing materials derived from adhesives, etc. Next, the sample powder is washed and filtered with ion exchange water and dried at 200°C for 1 hour. Thereafter, it is heated at 900°C in an oxygen atmosphere to remove the S-containing conductive layer, so that only the composite particles can be separated. It should be noted that the fully discharged state refers to a state where the depth of discharge (DOD) is 90% or more (the state of charge (SOC) is 10% or less).

[0039] <Ion-conducting phase>

[0040] The ion-conducting phase forms a matrix in which the silicon phase is dispersed. The ion-conducting phase may be, for example, a silicate phase or an amorphous carbon layer.

[0041] The silicate phase is composed of a compound containing a metal element, silicon (Si) and oxygen (O). The metal element is not particularly limited, but by containing at least lithium, for example, lithium ions can be easily introduced into and out of the silicate phase. That is, the silicate phase preferably contains at least lithium silicate.

[0042] Lithium silicate is a silicate containing lithium (Li), silicon (Si) and oxygen (O). The atomic ratio of O to Si in lithium silicate: O / Si is, for example, greater than 2 and less than 4. When the O / Si ratio is greater than 2 and less than 4 (z in the formula described below is 0<z<2), it is advantageous from the perspective of the stability of the silicate phase and lithium ion conductivity. Preferably, the O / Si ratio is greater than 2 and less than 3. In addition, the atomic ratio of Li to Si in lithium silicate: Li / Si is, for example, greater than 0 and less than 4.

[0043] The composition of lithium silicate can be expressed by the formula: Li 2z SiO 2+z (0<z<2). From the viewpoints of stability, ease of preparation, lithium ion conductivity, etc., z preferably satisfies the relationship of 0<z<1, and z=1 / 2 is more preferred. Lithium silicates satisfying z=1 / 2 can be Li 2 Si 2 O 5 The lithium silicate preferably contains Li 2 Si 2 O 5 As the main component, Li 2 Si 2 O 5 Here, the term "main component" refers to a component that accounts for 50% by mass or more of the total mass of the lithium silicate or the total mass of the silicate phase, and may also be a component that accounts for 70% by mass or more.

[0044] The silicate phase may contain other elements in addition to Li, Si, and O. By causing the silicate phase to contain other elements, chemical stability and lithium ion conductivity of the silicate phase are improved, or a side reaction caused by contact between the silicate phase and the nonaqueous electrolyte is suppressed.

[0045] The silicate phase may contain, as an element other than Li, Si, and O, at least one element selected from the group consisting of alkali metal elements (except lithium) and Group II elements.

[0046] By making the silicate phase contain an alkali metal element other than Li, crystallization becomes difficult, the viscosity in the softened state becomes low, and the fluidity becomes high. As a result, in the heat treatment process, it is easy to fill the gaps between silicon particles and easily generate dense composite particles. Alkali metal elements are cheap, so Na and / or K are preferred.

[0047] In addition, the silicate phase is usually alkaline, but the Group II elements have the effect of inhibiting the dissolution of alkali metals from the silicate phase. Therefore, if the silicate phase contains Group II elements, the viscosity of the slurry is easily stabilized when preparing a slurry containing a negative electrode active material. As a result, the necessity of treatment (such as acid treatment) for neutralizing the alkaline component of the composite particles is also reduced. The Group II element can be any of Ca or Mg. Among them, Ca is preferred from the viewpoint of increasing the Vickers hardness of the silicate phase and further improving the cycle characteristics.

[0048] In addition, in the silicate phase, as other elements M other than Li, Si and O, at least one selected from the group consisting of boron (B), aluminum (Al), zirconium (Zr), niobium (Nb), tantalum (Ta), vanadium (V), lanthanum (La), yttrium (Y), titanium (Ti), phosphorus (P), bismuth (Bi), zinc (Zn), tin (Sn), lead (Pb), antimony (Sb), cobalt (Co), erbium (Er), fluorine (F) and tungsten (W) may be included. From the viewpoint of resistance to non-aqueous electrolytes and structural stability of the silicate phase, the element M preferably includes at least one selected from the group consisting of Zr, Ti, P, Al and B.

[0049] The silicate phase may also contain rare earth elements. By including rare earth elements in the silicate phase, the charge and discharge efficiency at the beginning of the charge and discharge cycle can be improved. The rare earth element may also be any of scandium (Sc), yttrium (Y) and lanthanum. Among the above-mentioned elements M, lanthanum (La), yttrium (Y) and erbium (Er) are rare earth elements. As a rare earth element other than the above-mentioned element M, the silicate phase may also contain at least one selected from the group consisting of cerium (Ce), praseodymium (Pr) and neodymium (Nd). From the viewpoint of improving lithium ion conductivity, the rare earth element more preferably contains La. The proportion of La in the total rare earth elements is preferably greater than 90 atomic % and less than 100 atomic %.

[0050] As other elements M other than alkali metal elements and Group II elements, for example, B is advantageous in terms of low melting point and improved fluidity during sintering. Al, Zr and La can improve hardness while maintaining ion conductivity. In addition, Zr, Ti, P, Al and B have the effect of improving resistance to non-aqueous electrolytes and structural stability of silicate phases.

[0051] The silicate phase may further contain trace amounts of elements such as iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), and molybdenum (Mo).

[0052] The element M may form a compound. The compound may be, for example, a silicate of the element M or an oxide of the element M, depending on the type of the element M.

[0053] In the silicate phase, the content of the element M is, for example, 1 mol % or more and 40 mol % or less relative to the total amount of elements other than oxygen.

[0054] The contents of Li, Si, and the element M in the silicate phase can be measured, for example, by analyzing a cross section of the negative electrode mixture layer.

[0055] First, the battery in a fully discharged state is disassembled, the negative electrode is taken out, the negative electrode is cleaned with anhydrous methyl ethyl carbonate or dimethyl carbonate, the non-aqueous electrolyte component is removed and dried, and then the cross section of the negative electrode mixture layer is obtained using a cross-section polisher (CP). Then, the cross section of the negative electrode mixture layer is observed using a scanning electron microscope (SEM).

[0056] Next, the content of each element is determined by any of the following methods. Next, the composition of the silicate phase is calculated from the content of each element.

[0057] <EDX>

[0058] From the cross-sectional image of the reflected electron image of the negative electrode mixture layer, 10 composite particles with a maximum diameter of 5 μm or more are randomly selected, and element mapping analysis based on energy dispersive X-ray (EDX) is performed on each of them. The area ratio of the element to be the object is calculated using image analysis software. The observation magnification is preferably 2000 to 20000 times. The measured values ​​of the area ratio of the prescribed elements contained in the 10 particles are averaged. The content of the element to be the object is calculated from the obtained average value.

[0059] Preferred measurement conditions for cross-sectional SEM-EDX analysis are shown below.

[0060] <SEM-EDX measurement conditions>

[0061] Processing equipment: JEOL, SM-09010 (Cross Section Polisher)

[0062] Processing conditions: Acceleration voltage 6kV

[0063] Current value: 140μA

[0064] Vacuum degree: 1×10 -3 ~2×10 -3 Pa

[0065] Measuring device: Electron microscope SU-70 manufactured by HITACHI

[0066] Accelerating voltage during analysis: 10kV

[0067] Field: Free Mode

[0068] Probe current mode: Medium

[0069] Probe current range: High

[0070] Anode Ap.: 3

[0071] OBJ Ap.:2

[0072] Analysis area: 1μm square

[0073] Analysis software: EDAX Genesis

[0074] CPS: 20500

[0075] Lsec: 50

[0076] Time constant: 3.2

[0077] <AES>

[0078] From the cross-sectional image of the reflected electron image of the negative electrode mixture layer, 10 composite particles with a maximum diameter of 5 μm or more are randomly selected, and the elements are qualitatively and quantitatively analyzed using an Auger electron spectroscopy (AES) analyzer (e.g., JAMP-9510F manufactured by JEOL Ltd.). The measurement conditions can be set to, for example, an acceleration voltage of 10 kV, a beam current of 10 nA, and an analysis area of ​​20 μmφ. The content of the specified element contained in the 10 particles is averaged to calculate the content.

[0079] It should be noted that, during the charge and discharge process, a coating is formed on the surface of the composite particles due to the decomposition of the electrolyte. The mapping analysis based on EDX or AES is performed on the range of 1 μm inside the periphery of the composite particle cross section in a manner that does not include a thin coating or a conductive layer in the measurement range. At the end of the cycle, it is difficult to determine whether it is a decomposition product of the electrolyte, so it is preferred to measure the sample before or at the beginning of the cycle.

[0080] <ICP>

[0081] The composite particle sample was completely dissolved in a heated acid solution (a mixed acid of hydrofluoric acid, nitric acid, and sulfuric acid), and the carbon residue in the solution was filtered and removed. The obtained filtrate was then analyzed by inductively coupled plasma emission spectrometry (ICP) to measure the spectral intensity of each element. Next, a standard curve was prepared using a commercially available standard solution of the element to calculate the content of each element contained in the composite particle.

[0082] The quantitative analysis of other elements can also be performed using electron probe microanalyzer (EPMA), laser ablation ICP mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy (XPS), and the like.

[0083] The contents of B, Na, K, and Al contained in the silicate phase can be quantitatively analyzed in accordance with JIS R3105 (1995) (analysis method of borosilicate glass).

[0084] Silicate phase and silicon phase exist in the composite particles. The Si content obtained in the above method is the sum of the amount of Si constituting the silicon phase and the amount of Si in the silicate phase. On the other hand, the amount of Si constituting the silicon phase can also be quantified using Si-NMR. Thus, by using Si-NMR, the amount of Si constituting the silicon phase can be distinguished from the amount of Si in the silicate phase and quantified. It should be noted that as a standard substance necessary for quantification, a mixture of a silicate phase and a silicon phase containing a known Si content in a specified ratio can be used.

[0085] Preferred Si-NMR measurement conditions are shown below.

[0086] <Si-NMR measurement conditions>

[0087] Measuring device: Varian Inc., solid-state nuclear magnetic resonance spectrometer (INOVA-400)

[0088] Probe: Varian 7mm CPMAS-2

[0089] MAS: 4.2kHz

[0090] MAS speed: 4kHz

[0091] Pulse: DD (45° pulse + signal reading time 1H decoupling)

[0092] Repeat time: 1200 seconds to 3000 seconds

[0093] Observation width: 100kHz

[0094] Observation center: around -100ppm

[0095] Signal reading time: 0.05 seconds

[0096] Cumulative number of times: 560

[0097] Sample volume: 207.6 mg

[0098] The ion-conducting phase may be an amorphous carbon phase. That is, the composite particles may be composite particles comprising an amorphous carbon phase and a silicon phase (silicon particles) dispersed in the amorphous carbon phase. The amorphous carbon phase has conductivity, so even if voids are formed around such composite particles, it is easy to maintain the contact between the composite particles and their surroundings. As a result, the reduction in capacity caused by repeated charge and discharge cycles is easily suppressed. The amorphous carbon phase may be composed of hard carbon, soft carbon, or other than these. Amorphous carbon generally refers to the average plane spacing d of the (002) plane measured by X-ray diffraction. 002 Carbon materials larger than 0.34nm.

[0099] The average particle size of the composite particles having an amorphous carbon phase can be 3 μm or more and 18 μm or less, 6 μm or more and 15 μm or less, or 8 μm or more and 12 μm or less. The content of the silicon phase (silicon particles) in the composite particles having an amorphous carbon phase can be 30% or more and 80% or less by mass, or 40% or more and 70% or less by mass. In such a range, it is possible to achieve a sufficiently high capacity of the negative electrode, and the cycle characteristics are also easily improved.

[0100] The carbon content and sulfur content contained in the composite particles can also be measured using a carbon / sulfur analyzer (for example, EMIA-520 manufactured by Horiba, Ltd.). A sample is measured on a magnetic plate, a combustion aid is added, and the sample is inserted into a combustion furnace (carrier gas: oxygen) heated to 1350°C. The amount of carbon dioxide gas or sulfur oxide gas generated during combustion is detected by infrared absorption. In the case of carbon dioxide gas, for example, a standard curve is prepared using carbon steel (carbon content 0.49%) manufactured by Bureau of Analysed Samples. Ltd., and the carbon content of the sample is calculated (high-frequency induction heating furnace combustion-infrared absorption method). In the case of sulfur oxide gas, a standard curve is prepared using, for example, JSS245-6, a special steel for sulfur quantification provided by the Japan Iron and Steel Federation, to calculate the sulfur content.

[0101] The oxygen content contained in the composite particles can also be measured using an oxygen / nitrogen / hydrogen analyzer (e.g., EGMA-830 manufactured by Horiba, Ltd.). The sample is added to a Ni capsule and placed in a carbon crucible heated at 5.75 kW together with Sn pellets and Ni pellets that become flux, and the released carbon monoxide gas is detected. The standard curve uses standard sample Y 2 O 3The oxygen content of the sample was prepared and calculated (inert gas fusion-non-dispersive infrared absorption method).

[0102] <Silicon phase>

[0103] The silicon phase is a phase of silicon (Si) monomers, which repeatedly absorbs and releases lithium ions as the battery is charged and discharged. The capacity is expressed through the Faraday reaction in which the silicon phase participates. The silicon phase has a large capacity, so the expansion and contraction degree accompanying charging and discharging is also large. However, the silicon phase is dispersed in the ion conductive phase, so the stress caused by the expansion and contraction of the silicon phase is relaxed.

[0104] The silicon phase can be composed of a plurality of crystallites. The crystallite size of the silicon phase is preferably less than 30 nm. When the crystallite size of the silicon phase is less than 30 nm, the volume change caused by the expansion and contraction of the silicon phase accompanying charge and discharge can be reduced, and the cycle characteristics can be further improved. For example, when the silicon phase shrinks, the isolation of the silicon phase caused by the formation of voids around the silicon phase is suppressed, and the reduction in charge and discharge efficiency is suppressed. There is no particular limitation on the lower limit of the crystallite size of the silicon phase, for example, it is greater than 1 nm. The crystallite size of the silicon phase is more preferably greater than 10 nm and less than 30 nm, and more preferably greater than 15 nm and less than 25 nm. When the crystallite size of the silicon phase is greater than 10 nm, the surface area of ​​the silicon phase can be suppressed to be small, so it is difficult to produce degradation of the silicon phase accompanied by the generation of irreversible capacity. When the crystallite size of the silicon phase is less than 30 nm, it is easy to homogenize the expansion and contraction of the silicon phase, and the stress generated by the composite particles is easily relaxed, which can improve the cycle characteristics. The crystallite size of the silicon phase was calculated from the half-value width of the diffraction peak attributed to the (111) plane of the silicon phase (simple Si) in the X-ray diffraction pattern using the Scherrer equation.

[0105] The silicon phase of the composite particles contained in the battery before the first charge is, for example, granular. The average particle size of the granular silicon phase is preferably less than 500nm, more preferably less than 200nm, and further preferably less than 50nm. After the first charge, the average particle size of the silicon phase is preferably less than 400nm, more preferably less than 100nm. By miniaturizing the silicon phase, the volume change of the composite particles during charge and discharge becomes smaller, and the structural stability of the composite particles is further improved. The average particle size of the silicon phase is measured using a cross-sectional image of the composite particles obtained by SEM. Specifically, the average particle size of the silicon phase is obtained by averaging the maximum diameters of any 100 silicon phases.

[0106] From the viewpoint of high capacity, the content of the silicon phase in the composite particles is preferably 30% by mass or more, more preferably 35% by mass or more, and further preferably 55% by mass or more. In this case, the diffusibility of lithium ions is good, and excellent load characteristics can be obtained. On the other hand, from the viewpoint of improving cycle characteristics, the content of the silicon phase in the composite particles is preferably 95% by mass or less, more preferably 75% by mass or less, and further preferably 70% by mass or less. In this case, the surface of the silicon phase that is not covered by the silicate phase and exposed is reduced, and the side reaction of the non-aqueous electrolyte and the silicon phase is easily suppressed.

[0107] <S-containing conductive layer>

[0108] The S-containing conductive layer is disposed on the surface of the composite particles. The S-containing conductive layer imparts conductivity to the composite particles. That is, the S-containing conductive layer constitutes a part of the conductive network in the negative electrode. For example, even when the conductivity of the ion-conducting phase is low, such as a silicate phase, the composite particles having the conductive layer have conductivity, so the current collection of the negative electrode is improved.

[0109] The S-containing conductive layer covers at least a portion of the surface of the composite particles. Therefore, the S-containing conductive layer also acts as a barrier layer that suppresses the side reactions of the non-aqueous electrolyte and the composite particles, and suppresses the side reactions of the electrolyte decomposition products and the composite particles. Among them, the electrolyte decomposition products (especially HF) easily degrade the ion conduction phase. In contrast, the sulfur component contained in the S-containing conductive layer reacts with the components of the electrolyte or the electrolyte decomposition products to form a stable coating. As a result, the degradation of the ion conduction phase is significantly suppressed, and the reduction of the charge and discharge cycle characteristics is suppressed.

[0110] From the viewpoint of ensuring capacity, the S-containing conductive layer is preferably thin enough not to substantially affect the average particle size of the composite particles. If the conductivity and the diffusivity of lithium ions are taken into account, the thickness of the S-containing conductive layer is preferably greater than 1 nm and less than 200 nm, more preferably greater than 5 nm and less than 100 nm. The thickness of the conductive layer can be measured by cross-sectional observation of the composite particles obtained using SEM or TEM. Specifically, the thickness of the S-containing conductive layer of any 10 composite particles having a conductive layer is averaged and obtained. Among them, the thickness of the S-containing conductive layer is obtained by measuring the thickness of any 10 locations of each composite particle and averaging.

[0111] The mass ratio of the S-containing conductive layer to the total of the composite particles and the S-containing conductive layer may be 0.5 mass % to 10 mass % or more, or 1 mass % to 5 mass % or less.

[0112] The S-containing conductive layer comprises a conductive material and an S component dispersed in the conductive material. As the conductive material, a carbon material is preferred. As the carbon material, amorphous carbon, graphite, easily graphitized carbon (soft carbon), difficultly graphitized carbon (hard carbon), etc. can be used. Among them, from the viewpoint of easily forming a thin conductive layer covering the surface of the composite particles, amorphous carbon is preferred. As amorphous carbon, carbon black, a roasted product of asphalt, coke, activated carbon, etc. can be listed. As graphite, natural graphite, artificial graphite, graphitized mesophase carbon, etc. can be listed.

[0113] Examples of the S component include sulfuric acid compounds such as sulfates and sulfate esters. The S component may be a sulfonic acid group (-SO 3 H), -SH group, -SO 2 A substance in which a functional group containing sulfur, such as a - group, is bonded to a carbon atom of a carbon material.

[0114] Even a trace amount of the S component contained in the S-containing conductive layer can react with the electrolyte decomposition product to inhibit the degradation of the ion conduction phase. Therefore, there is no particular restriction on the content of S contained in the S-containing conductive layer as long as the function as the conductive layer is not greatly damaged. As long as the S component can be detected from the S-containing conductive layer. The amount of S contained in the S-containing conductive layer is preferably 0.02% or more and 1% or less, for example, relative to the mass of the silicon-containing material (the total of the S-containing conductive layer and the composite particles), and can also be 0.02% or more and 0.8% or less, and can also be 0.03% or more and 0.5% or less.

[0115] The presence of the S component in the S-containing conductive layer can be confirmed by, for example, analyzing the cross section of the composite particle having the S-containing conductive layer by electron energy loss spectroscopy (TEM-EELS) to confirm the presence or absence of a peak derived from the S-containing group or the S-containing compound. When the inside of the composite particle is analyzed, if the TEM-EELS loss spectrum does not have a peak derived from the S-containing group or the S compound, it can be said that the S component is selectively contained in the S-containing conductive layer.

[0116] The content of sulfur contained in the conductive layer can be obtained by heating the silicon-containing material separated from the battery in an oxygen atmosphere in a carbon / sulfur analyzer using the above-mentioned method, and detecting the amount of sulfur oxide gas generated during combustion. When the silicon-containing material has a silicate phase, the mass of the sulfur-containing conductive layer is obtained by subtracting the mass of the composite particles after the sulfur-containing conductive layer is burned from the mass of the silicon-containing material, thereby obtaining the content ratio N. 1 and N 2 .

[0117] The following situation can also be considered: when the ion-conducting phase is an amorphous carbon phase and the S-containing conductive layer contains an amorphous carbon material, it is difficult to determine the boundary between the composite particles in the silicon-containing material and the S-containing conductive layer, and it is difficult to derive the thickness of the S-containing conductive layer. In this case, it is sufficient that the region from the surface of the silicon-containing material to the surface layer of at least 100 nm contains sulfur. The ion-conducting phase may also contain sulfur.

[0118] [Method for producing silicon-containing material]

[0119] Next, an example of a method for producing a silicon-containing material is described in detail. The silicon-containing material can be obtained by forming an S-containing conductive layer on composite particles. The composite particles can be produced by, for example, the following production method including the first to fourth steps.

[0120] (First step) A step of obtaining a compound that forms an ion-conducting phase.

[0121] (Second step) After the first step, a step of compositeing the compound forming the ion conductive phase with the raw material silicon to disperse the silicon phase in the ion conductive phase to obtain a composite intermediate.

[0122] (Third step) A step of subjecting the composite intermediate to heat treatment to obtain a sintered body including an ion conductive phase and a silicon phase dispersed in the ion conductive phase.

[0123] (Fourth step) A step of pulverizing the sintered body to obtain composite particles including an ion conductive phase and a silicon phase dispersed in the ion conductive phase.

[0124] <1st step>

[0125] In the first step, a compound that forms an ion-conducting phase is prepared or synthesized. When an amorphous carbon phase is used as an ion-conducting phase, a carbon source may be prepared. The carbon source may or may not be amorphous. After the subsequent compounding (second step) and sintering (third step), the carbon source changes into an amorphous carbon phase.

[0126] As the carbon source, there can be used, for example, water-soluble resins such as carboxymethyl cellulose (CMC), hydroxyethyl cellulose, polyacrylic acid salts, polyacrylamide, polyvinyl alcohol, polyethylene oxide, polyvinyl pyrrolidone; sugars such as cellulose and sucrose; petroleum pitch, coal tar pitch, tar, etc., without particular limitation.

[0127] As the carbon source, graphite, graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon black, etc. can also be used. As carbon black, acetylene black, Ketjen black, etc. can be listed. Even when graphite is used as the carbon source, when a composite of silicon particles and the carbon source is obtained using a pulverizing device, the crystal structure of the graphite is almost lost, thereby forming an amorphous carbon phase.

[0128] When the silicate phase is used as the ion-conducting phase, the first step includes, for example, step 1a of mixing silicon dioxide and a lithium compound to obtain a raw material mixture; and step 1b of calcining the raw material mixture to obtain a raw silicate. The raw material mixture may also contain the above-mentioned element M. The calcination in step 1b is performed in, for example, an oxidizing atmosphere. The calcination temperature in step 1b is preferably 400° C. or higher and 1200° C. or lower, and more preferably 800° C. or higher and 1100° C. or lower.

[0129] The raw material mixture is dissolved, and the melt is passed through a metal roller to be flaked, thereby producing lithium silicate. Afterwards, the flaked silicate is heat-treated in an atmospheric atmosphere at a temperature above the glass transition temperature and below the melting point to crystallize it. It should be noted that the flaked silicate can also be used without crystallization. In addition, the mixture mixed in a specified amount can also be calcined at a temperature below the melting point without dissolving, thereby producing silicate by a solid phase reaction.

[0130] Examples of the lithium compound include lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. The lithium compound may be used alone or in combination of two or more.

[0131] As the compound containing the element M, oxides, hydroxides, hydrides, halides, carbonates, oxalates, nitrates, sulfates, etc. of the element M can be used. As the compound containing the element M, one kind can be used alone, or two or more kinds can be used in combination.

[0132] <Step 2>

[0133] The second step includes, for example, a step of applying shear force to a mixture of a compound forming an ion-conducting phase (e.g., a carbon source or a raw silicate) and raw silicon and crushing the mixture to obtain a finely granulated composite intermediate. Here, for example, the compound forming an ion-conducting phase and raw silicon are mixed in a predetermined mass ratio, and a crushing device such as a ball mill is used to stir the mixture while finely granulating the mixture. An organic solvent may also be added to the mixture for wet crushing. At this time, the raw silicon is finely crushed to generate a silicon phase. The silicon phase is dispersed in the matrix of the compound forming the ion-conducting phase.

[0134] As the organic solvent, alcohol, ether, fatty acid, alkane, cycloalkane, silicate, metal alkoxide, etc. can be used. A predetermined amount of organic solvent can be added to the pulverizing container at once at the initial stage of pulverization, or a predetermined amount of organic solvent can be added to the pulverizing container intermittently in multiple times during the pulverization process. The organic solvent plays a role in preventing the pulverized object from adhering to the inner wall of the pulverizing container.

[0135] As raw silicon, coarse silicon particles with an average particle size of several μm to several tens of μm may also be used. The silicon phase finally obtained is preferably controlled so that the crystallite size is 10 nm or more, and the crystallite size is calculated by the Scherrer formula from the half-value width of the diffraction peak attributable to the Si (111) plane of the X-ray diffraction pattern.

[0136] It should be noted that the second step is not limited to the above. For example, the compound forming the ion conductive phase and the raw silicon may be finely granulated and mixed. In addition, silicon nanoparticles and raw silicate nanoparticles may be synthesized without using a pulverizing device and mixed. The nanoparticles may be prepared by a known method such as a gas phase method (e.g., a plasma method) or a liquid phase method (e.g., a liquid phase reduction method).

[0137] <Step 3>

[0138] The third step includes, for example, a step of calcining the finely granulated composite intermediate while applying pressure by hot pressing or the like to obtain a sintered body. The calcination of the composite intermediate is performed in, for example, an inert atmosphere (eg, an argon or nitrogen atmosphere).

[0139] When the amorphous carbon phase is used as the ion conductive phase, the carbon source is carbonized to generate amorphous carbon by heating at 700° C. to 1200° C. in an inert atmosphere. Thus, composite particles in which the silicon phase is dispersed in the amorphous carbon phase as the ion conductive phase are obtained.

[0140] When the silicate phase is used as the ion-conducting phase, the calcination temperature is preferably above 450°C and below 1000°C. In the case of the above temperature range, it is easy to disperse tiny silicon phases in the silicate phase with low crystallinity. The raw silicate is stable in the above temperature range and hardly reacts with silicon. The calcination temperature is preferably above 550°C and below 900°C, and more preferably above 650°C and below 850°C. The calcination time is, for example, above 1 hour and below 10 hours. During sintering, the silicate softens and flows in a manner that fills the gaps between the silicon particles. As a result, a dense block-shaped sintered body can be obtained in which the silicate phase as the ion-conducting phase is used as the sea and the silicon phase is dispersed in the form of islands in the silicate phase.

[0141] <Step 4>

[0142] The fourth step is a step of pulverizing the sintered body so as to have a desired particle size distribution, thereby obtaining composite particles including a silicate phase and a silicon phase dispersed in the silicate phase. The composite particles are pulverized so as to have an average particle size of, for example, 1 to 25 μm.

[0143] <Step of forming a S-containing conductive layer>

[0144] Next, an example of a process for forming a S-containing conductive layer on the composite particles is described. As the raw material of the conductive material forming the conductive layer, for example, coal tar pitch or coal tar pitch, petroleum pitch, phenolic resin, etc. can be used. The raw material of the conductive material is mixed with the composite particles, and the mixture is calcined to carbonize the raw material of the conductive material, thereby forming a conductive layer covering at least a portion of the surface of the composite particles.

[0145] Here, the raw material of the conductive material is mixed with the raw material of the S component, and the mixture is calcined to form the S-containing conductive layer. As the raw material of the S component, sulfuric acid compounds or sulfonic acid compounds can be listed. The sulfuric acid compound or sulfonic acid compound can be a salt compound or an ester compound. The cation of the salt compound can be an inorganic cation such as a metal ion or an organic cation. As the raw material of the S component, for example, CaSO 4 .

[0146] A raw material of the conductive material containing an S component may also be used. For example, coal tar pitch containing a large amount of S may also be used.

[0147] The calcination of the mixture of the raw material of the conductive material and the composite particles can be carried out in, for example, an inert atmosphere (for example, an atmosphere such as argon or nitrogen). The calcination temperature is preferably 450° C. or higher and 1000° C. or lower. In the case of the above temperature range, it is easy to form a highly conductive S-containing conductive layer in a silicate phase with low crystallinity. The calcination temperature is preferably 550° C. or higher and 900° C. or lower, more preferably 650° C. or higher and 850° C. or lower. The calcination time is, for example, 1 hour or higher and 10 hours or lower.

[0148] The S-containing conductive layer can also be formed on the composite particles by other methods. For example, a gas phase method such as a CVD method can be used to react hydrocarbon gas with a compound containing S on the surface of the composite particles to form the S-containing conductive layer. As the hydrocarbon gas, acetylene, methane, etc. can be used. In addition, carbon black and a compound containing S can be mixed with the composite particles together, so that a precursor of the S-containing conductive layer is attached to the surface of the composite particles, and then the precursor of the S-containing conductive layer is baked together with the composite particles to form the S-containing conductive layer.

[0149] Hereinafter, an example of a negative electrode material for a secondary battery according to an embodiment of the present invention will be described with reference to Figure 1 While explaining. Figure 1 1 is a diagram schematically showing a cross section of a composite particle 11. The composite particle 11 includes a silicate phase 12, a silicon (Si monomer) phase 13 dispersed in the silicate phase 12, and a compound 14 of an element M as an arbitrary component. At least a portion of the surface of the composite particle 11 is covered with a conductive layer 15 containing S.

[0150] The composite particle 11 has, for example, an island structure, and in any cross section, in the matrix of the silicate phase 12, the fine silicon phase 13 is not unevenly distributed in a part of the region, but is dispersed roughly uniformly. It should be noted that the silicate phase 12 may also contain SiO2 to the extent of a natural oxide film formed on the surface of the silicon phase. 2 .

[0151] Figure 2 1 is a schematic diagram showing a cross section of a battery using the composite particle 11 covered with a S-containing conductive layer as a negative electrode active material, after several cycles of charge and discharge. Figure 1 The adjacent granular silicon phases 13 are connected to each other and can form a network-like silicon phase 16 .

[0152] (Secondary battery)

[0153] The secondary battery of the embodiment of the present disclosure has a positive electrode, a negative electrode and an electrolyte, and the negative electrode comprises a carbon material and the negative electrode material for the secondary battery. A separator is usually sandwiched between the positive electrode and the negative electrode. Both the carbon material and the negative electrode material for the secondary battery are used as negative electrode active materials, which contribute to the absorption and release of cations (such as lithium ions) accompanying charging and discharging. The secondary battery can also be a non-aqueous electrolyte secondary battery.

[0154] Hereinafter, the secondary battery will be described in detail.

[0155] [negative electrode]

[0156] The negative electrode may also include: a negative electrode current collector and a negative electrode mixture layer supported on the surface of the negative electrode current collector. The negative electrode mixture layer may be formed by applying a negative electrode slurry obtained by dispersing a negative electrode mixture in a dispersion medium to the surface of the negative electrode current collector and drying it. The dried coating may also be rolled as needed. The negative electrode mixture layer may be formed on the surface of one side of the negative electrode current collector or on the surfaces of both sides.

[0157] The negative electrode mixture may include a negative electrode active material as an essential component and a binder, a conductive agent, a thickener, etc. as an optional component. The negative electrode active material includes the above-mentioned negative electrode material (composite particles having a conductive layer). The composite particles can absorb a large amount of lithium ions in the silicon phase, thus contributing to the high capacity of the negative electrode.

[0158] The negative electrode active material preferably further comprises a carbon material that can electrochemically absorb and release lithium ions. The composite particles having a conductive layer will expand and shrink in volume with charging and discharging, so when the ratio of the composite particles in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is likely to occur with charging and discharging. On the other hand, by combining the composite particles having a conductive layer and the carbon material, it is possible to impart a high capacity of the silicon phase to the negative electrode and achieve excellent cycle characteristics. From the viewpoint of high capacity and improved cycle characteristics, the ratio B / A of the mass B of the composite particles (silicon-containing material) having a conductive layer to the mass A of the carbon material satisfies 0.05≤B / A≤0.3.

[0159] As carbon materials, examples include graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon). Among them, graphite having excellent charge and discharge stability and low irreversible capacity is preferred. Graphite refers to a material having a graphite-type crystal structure, and may include, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon material may be used alone, or two or more carbon materials may be used in combination.

[0160] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.), a porous conductive substrate (mesh, net, punching sheet, etc.) can be used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified. There is no particular limitation on the thickness of the negative electrode current collector. From the perspective of balancing the strength and lightness of the negative electrode, it is preferably 1 to 50 μm, and more preferably 5 to 20 μm.

[0161] Examples of the adhesive include resin materials such as fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aromatic polyamide resins; polyimide resins such as polyimide and polyamideimide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymers; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinyl pyrrolidone; polyether sulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. The adhesive may be used alone or in combination of two or more.

[0162] Examples of the conductive agent include carbons such as acetylene black, conductive fibers such as carbon fibers and metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene derivatives. The conductive agent may be used alone or in combination of two or more.

[0163] Examples of thickeners include carboxymethyl cellulose (CMC) and modified forms thereof (including salts such as Na salts), cellulose derivatives such as methyl cellulose (cellulose ethers, etc.), saponified polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide), etc. The thickeners may be used alone or in combination of two or more.

[0164] The dispersion medium is not particularly limited, and examples thereof include water, alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0165] [positive electrode]

[0166] The positive electrode may include a positive electrode collector and a positive electrode mixture layer supported on the surface of the positive electrode collector. The positive electrode mixture layer may be formed by applying a positive electrode slurry obtained by dispersing the positive electrode mixture in a dispersion medium to the surface of the positive electrode collector and drying it. The dried coating may also be rolled as needed. The positive electrode mixture layer may be formed on the surface of one side of the positive electrode collector or on the surfaces of both sides. The positive electrode mixture may contain a positive electrode active material as an essential component and a binder, a conductive agent, etc. as an optional component. As a dispersion medium for the positive electrode slurry, NMP or the like may be used.

[0167] As the positive electrode active material, for example, a composite oxide containing lithium can be used. For example, a material selected from the group consisting of Li a CoO 2 , Li a NiO 2 , Li a MnO 2 , Li a Co b Ni 1-b O 2 , Li a Co b Me 1-b O c , Li a Ni 1-b Me b O c , Li a Mn 2 O 4 , Li a Mn 2- b Me b O 4 、LiMePO 4 , Li 2 MePO 4F (Me is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B). Here, a=0 to 1.2, b=0 to 0.9, and c=2.0 to 2.3. It should be noted that the value a indicating the molar ratio of lithium increases or decreases by charge and discharge.

[0168] As the binder and the conductive agent, the same substances as those exemplified for the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite can be used.

[0169] The shape and thickness of the positive electrode current collector can be selected according to the shape and thickness of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, and the like.

[0170] [Electrolytes]

[0171] The electrolyte includes a solvent and a lithium salt dissolved in the solvent. The concentration of the lithium salt in the electrolyte is, for example, 0.5 to 2 mol / L. The electrolyte may also contain known additives. By setting the lithium salt concentration within the above range, a non-aqueous electrolyte having excellent ion conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0172] The solvent uses an aqueous solvent or a non-aqueous solvent. As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, etc. can be used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be listed. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be listed. As cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be listed. As chain carboxylates, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, etc. can be listed. The non-aqueous solvent can be used alone or in combination of two or more.

[0173] Examples of lithium salts include LiClO 4 , LiBF 4 、LiPF 6 、LiAlCl 4 、LiSbF 6 、LiSCN、LiCF 3 SO 3 、LiCF 3 CO 2 、LiAsF 6 , LiB 10 Cl 10, lithium lower aliphatic carboxylates, LiCl, LiBr, LiI, borates, imide salts, etc. Examples of borates include lithium bis(1,2-benzenediol (2-)-O,O')borate, lithium bis(2,3-naphthoic acid (2-)-O,O')borate, lithium bis(2,2'-biphenylediol (2-)-O,O')borate, and lithium bis(5-fluoro-2-phenol-1-benzenesulfonic acid-O,O')borate. Examples of imide salts include lithium bis(fluorosulfonyl imide) (LiN(FSO 2 ) 2 ), Lithium Bis(trifluoromethanesulfonyl)imide (LiN(CF 3 SO 2 ) 2 ), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF 3 SO 2 )(C 4 F 9 SO 2 ))、Lithium bis(pentafluoroethanesulfonate)imide (LiN(C 2 F 5 SO 2 ) 2 ) etc. Among them, LiPF 6 The lithium salt may be used alone or in combination of two or more.

[0174] As an electrolyte, a compound (sulfur compound) containing an S component may also be added. The sulfur compound is decomposed on the surface of the silicon-containing material, so that a film containing S can be formed on the surface of the silicon-containing material. The film containing S is strong and stable, and has the effect of inhibiting the dissolution of the ion-conducting phase and inhibiting the reduction of the charge-discharge cycle characteristics caused by the progress of side reactions. However, when the electrolyte contains sulfur compounds at high concentrations, it is easy to corrode the battery case. In addition, the following situation can also be considered: the film containing S can also be formed on the surface of the carbon material, so on the surface of the carbon material, the movement resistance of lithium ions increases, and the charge-discharge cycle characteristics are reduced instead.

[0175] In contrast, by using a silicon-containing material covered by a S-containing conductive layer, a film containing S is selectively formed on the surface of the silicon-containing material, and the formation of a film containing S on the surface of the carbon material is suppressed. Therefore, a compound (sulfur compound) containing an S component may not be added to the electrolyte. Thus, the effect of suppressing the reduction of the charge and discharge cycle characteristics is high, and the corrosion of the battery case is also suppressed. A silicon-containing material covered by a S-containing conductive layer can be used and a sulfur compound can be added to the electrolyte, but in order to suppress the corrosion of the battery case, the concentration of the sulfur compound in the electrolyte is preferably kept below 5% by mass.

[0176] As sulfur compounds added to the electrolyte, salts and sulfuric acid esters of sulfuric acid, salts and esters of sulfonic acid, sulfur-containing imides and their salts, etc. can be listed. As examples of sulfuric acid esters, cyclic sulfuric acid esters such as 1-propenyl-1,3-sultone (PRES) can be listed. As examples of sulfonic acid esters, cyclic sulfonic acid esters such as ethylene sulfide (ES) can be listed. As examples of sulfur-containing imide salts, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, etc. can be listed. Sulfuric acid and sulfonic acid, such as lithium fluorosulfonate, can be substances in which part of the oxygen bonded to the sulfur atom is replaced by fluorine.

[0177] [Separator]

[0178] Usually, a separator is preferably sandwiched between the positive electrode and the negative electrode. The separator has high ion permeability, moderate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, a polyolefin such as polypropylene, polyethylene, etc. can be used.

[0179] As an example of a secondary battery structure, an electrode group formed by winding an electrolyte with a positive electrode and a negative electrode across a separator can be listed as a structure obtained by being accommodated in an outer shell. However, it is not limited to this, and other forms of electrode groups can also be applied. For example, it can also be a stacked electrode group formed by stacking a positive electrode and a negative electrode across a separator. The secondary battery can be any form such as a cylindrical type, a square type, a coin type, a button type, a laminated type, etc.

[0180] Figure 3 This is a schematic perspective view showing a partially cutaway view of a square secondary battery according to an embodiment of the present disclosure.

[0181] The battery comprises: a square battery case 4 with a bottom, an electrode group 1 and an electrolyte (not shown) contained in the battery case 4, and a sealing plate 5 for sealing the opening of the battery case 4. The electrode group 1 comprises: a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched therebetween. The negative electrode, the positive electrode, and the separator are wound around a flat winding core, and the winding core is pulled out to form the electrode group 1. The sealing plate 5 comprises: a liquid injection port plugged by a sealing plug 8, and a negative terminal 6 insulated from the sealing plate 5 by a gasket 7.

[0182] One end of a negative electrode lead 3 is attached to the negative electrode current collector of the negative electrode by welding or the like. One end of a positive electrode lead 2 is attached to the positive electrode current collector of the positive electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative electrode terminal 6. The other end of the positive electrode lead 2 is electrically connected to the sealing plate 5. A resin frame is arranged on the upper part of the electrode group 1 to isolate the electrode group 1 from the sealing plate 5 and to isolate the negative electrode lead 3 from the battery case 4.

[0183] Postscript

[0184] The following techniques are disclosed through the description of the above embodiments.

[0185] (Technology 1)

[0186] A negative electrode material for a secondary battery, comprising a silicon-containing material, wherein the silicon-containing material comprises composite particles containing silicon and a conductive layer disposed on the surface of the composite particles.

[0187] The composite particles include an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase,

[0188] The conductive layer contains a sulfur component, and the content rate N of the sulfur element in the conductive layer is 1 It is 50 mass % or less.

[0189] (Technique 2)

[0190] According to the negative electrode material for a secondary battery of technique 1, the ratio N of the mass of the sulfur element contained in the conductive layer to the mass of the silicon-containing material is 2 It is 0.02% or more.

[0191] (Technique 3)

[0192] According to the negative electrode material for secondary battery of technology 2, wherein the ratio N 2 It is 0.02% or more and 1% or less.

[0193] (Technique 4)

[0194] The negative electrode material for a secondary battery according to any one of techniques 1 to 3, wherein the ion conductive phase is a silicate phase.

[0195] (Technique 5)

[0196] In the negative electrode material for a secondary battery according to technique 4, the silicate phase contains at least one element selected from the group consisting of alkali metal elements and Group II elements.

[0197] (Technique 6)

[0198] The negative electrode material for a secondary battery according to technology 4 or 5, wherein the silicate phase further contains element M,

[0199] The element M includes at least one selected from the group consisting of boron (B), aluminum (Al), zirconium (Zr), niobium (Nb), tantalum (Ta), vanadium (V), lanthanum (La), yttrium (Y), titanium (Ti), phosphorus (P), bismuth (Bi), zinc (Zn), tin (Sn), lead (Pb), antimony (Sb), cobalt (Co), erbium (Er), fluorine (F) and tungsten (W).

[0200] (Technique 7)

[0201] In the secondary battery negative electrode material according to any one of techniques 1 to 6, the ion conductive phase is an amorphous carbon phase.

[0202] (Technology 8)

[0203] A secondary battery comprising a positive electrode, a negative electrode and an electrolyte.

[0204] The negative electrode includes a carbon material and the negative electrode material for a secondary battery described in any one of Techniques 1 to 7.

[0205] (Technique 9)

[0206] The secondary battery according to technology 8, wherein a ratio B / A of a mass B of the silicon-containing material to a mass A of the carbon material satisfies 0.05≤B / A≤0.3.

[0207] (Technology 10)

[0208] The secondary battery according to technology 8 or 9, wherein the electrolyte does not contain a sulfur compound, or the electrolyte contains a sulfur compound at a concentration of 5 mass % or less.

[0209] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0210] (Example 1)

[0211] [Preparation of composite particles]

[0212] <1st step>

[0213] SiO2 and Li 2 CO 3 The mixture was mixed and calcined in air at 950° C. for 10 hours to obtain silicate. The obtained silicate was pulverized to have an average particle size of 10 μm.

[0214] <Second step>

[0215] Silicate was mixed with raw silicon (3N, average particle size 10 μm) in a mass ratio of 40:60.

[0216] The mixture was filled into a pot (SUS, capacity: 500 mL) of a planetary ball mill (Fritsch Japan Co., Ltd., P-5), 24 SUS balls (diameter 20 mm) were added to the pot and the pot lid was closed, and the mixture was pulverized at 200 rpm in an inert atmosphere for 50 hours.

[0217] <Step 3>

[0218] Next, the powdered mixture was taken out in an inert atmosphere, and calcined at 600° C. for 4 hours in an inert atmosphere under pressure with a hot press to obtain a sintered body of the mixture.

[0219] <Step 4>

[0220] Next, the obtained sintered body was pulverized and passed through a 40 μm mesh to obtain composite particles. The composition of the main component of the silicate phase in the composite particles obtained by the above method was Li 2 Si 2 O 5 .

[0221] <Step of forming a S-containing conductive layer>

[0222] Next, the composite particles, coal tar pitch and calcium sulfate were mixed in a mass ratio of 94.85:5:0.15, and then calcined at 800°C in an argon atmosphere to form a S-containing conductive layer covering at least a portion of the surface of the composite particles, thereby obtaining a silicon-containing material. By calcining, the coal tar pitch is converted into amorphous carbon.

[0223] The thickness of the S-containing conductive layer determined by the above method was 10 nm.

[0224] The mass ratio of the S-containing conductive layer to the total of the composite particles and the S-containing conductive layer was calculated from the mass difference of the composite particles before and after the formation of the S-containing conductive layer, and the result was 2.9 mass %. In addition, the S content N in the S-containing conductive layer calculated by the above method was 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 1.0 mass %. 2 It is 0.03%.

[0225] <Production of negative electrode>

[0226] The composite particles having a S-containing conductive layer and graphite were mixed in a mass ratio of 5:95 and used as the negative electrode active material. Water was added to a negative electrode mixture containing a negative electrode active material, a sodium salt of CMC, and SBR in a mass ratio of 97.5:1:1.5 and stirred to prepare a negative electrode slurry. Next, a layer of 100% slurry was added to the surface of the copper foil at a rate of 100% per m 2 The negative electrode slurry was applied so that the mass of the negative electrode mixture became 190 g, and the coating was dried and rolled to form a copper foil with a density of 1.5 g / cm on both sides. 3 The negative electrode of the negative electrode mixture layer.

[0227] <Production of positive electrode>

[0228] NMP was added to a positive electrode mixture containing lithium cobalt oxide, acetylene black and PVDF in a mass ratio of 95:2.5:2.5 and stirred to prepare a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of an aluminum foil, and the coating was dried and rolled to form a 3.6 g / cm2 film on both sides of the aluminum foil. 3 The positive electrode of the positive electrode mixture layer.

[0229] [Preparation of non-aqueous electrolyte]

[0230] LiPF was dissolved at a concentration of 1.0 mol / L in a mixed solvent containing EC and DEC in a volume ratio of 3:7. 6 , thereby preparing a non-aqueous electrolyte (electrolyte).

[0231] [Fabrication of non-aqueous electrolyte secondary battery]

[0232] The positive electrode and the negative electrode, each with a tab attached, were wound with a separator interposed therebetween to produce an electrode group with the tab located at the outermost periphery. The electrode group was inserted into an outer casing made of an aluminum laminate film, vacuum dried at 105° C. for 2 hours, and then a nonaqueous electrolyte was injected, and the opening of the outer casing was sealed to obtain Battery A1 of Example 1.

[0233] (Examples 2, 3, Comparative Examples 1, 2)

[0234] In the step of forming the S-containing conductive layer, the mixing ratio of the composite particles, coal tar pitch, and calcium sulfate was changed. The ratio of coal tar pitch to the entire mixture was kept constant, and the mixing ratio of the composite particles and calcium sulfate was changed.

[0235] In Example 2, the composite particles, coal tar pitch, and calcium sulfate were mixed in a mass ratio of 93:5:2, and the other steps were carried out in the same manner as in Example 1 to obtain Battery A2. S content N in the S-containing conductive layer 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 14.7% by mass. 2 It is 0.47%.

[0236] In Example 3, the composite particles, coal tar pitch and calcium sulfate were mixed in a mass ratio of 92:5:3, and the other steps were carried out in the same manner as in Example 1 to obtain a battery A2. S content N in the S-containing conductive layer 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 20.9 mass%. 2 It is 0.71%.

[0237] In Comparative Example 1, calcium sulfate was not added, and the composite particles and coal tar pitch were mixed at a mass ratio of 97:3. The other procedures were carried out in the same manner as in Example 1, thereby obtaining Battery B1.

[0238] In Comparative Example 2, the composite particles, coal tar pitch, and calcium sulfate were mixed in a mass ratio of 85:5:10, and the other procedures were the same as in Example 1 to obtain a battery B2. S content N in the S-containing conductive layer 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 51.2% by mass. 2 It is 2.66%.

[0239] (Example 4)

[0240] In the preparation of the non-aqueous electrolyte, lithium fluorosulfonate (FSL) was added to a mixed solvent containing EC and DEC at a volume ratio of 3:7 to give a concentration of 5 mass %, and LiPF was further added to a concentration of 1.0 mol / L. 6 The S content N in the S-containing conductive layer is 0.0447 W / m 2 0.0347 W / m 2 0.02 ... 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 1.1 mass %. 2 It is 0.03%.

[0241] (Example 5)

[0242] [Preparation of composite particles]

[0243] <1st step>

[0244] Graphitizable carbon (soft carbon) is prepared as a carbon source.

[0245] <Second step>

[0246] The carbon source and raw silicon (3N, average particle size 10 μm) were mixed. The mass ratio of the carbon source to the raw silicon in the mixture was 40:60.

[0247] The mixture was filled into a pot (SUS, capacity: 500 mL) of a planetary ball mill (Fritsch Japan Co., Ltd., P-5), 24 SUS balls (diameter 20 mm) were added to the pot and the pot lid was closed, and the mixture was pulverized at 200 rpm in an inert atmosphere for 50 hours.

[0248] <Step 3>

[0249] Next, the powdered mixture was taken out in an inert atmosphere, and calcined at 800° C. for 4 hours in an inert atmosphere under pressure with a hot press to obtain a sintered body of the mixture.

[0250] <Step 4>

[0251] Next, the obtained sintered body was pulverized and passed through a 40 μm mesh to obtain composite particles having an amorphous carbon phase.

[0252] <Step of forming a S-containing conductive layer>

[0253] Next, the composite particles, coal tar pitch and calcium sulfate were mixed in a mass ratio of 94.5:5:0.5, and then calcined at 800°C in an argon atmosphere to form a S-containing conductive layer covering at least a portion of the surface of the composite particles, thereby obtaining a silicon-containing material. By calcining, the coal tar pitch is converted into amorphous carbon.

[0254] The mass ratio of the S-containing conductive layer to the total of the composite particles and the S-containing conductive layer was calculated from the mass difference of the composite particles before and after the formation of the S-containing conductive layer, and the result was 2.8 mass %. In addition, the S content N in the S-containing conductive layer calculated by the above method was 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 3.9 mass%. 2 It is 0.11%.

[0255] Using the silicon-containing material obtained in this way, the subsequent steps were carried out in the same manner as in Example 1 to produce a negative electrode, thereby obtaining Battery A5 of Example 5.

[0256] (Example 6, Comparative Example 3)

[0257] In the step of forming the S-containing conductive layer, the mixing ratio of the composite particles, coal tar pitch and calcium sulfate was changed. In Example 6, the composite particles, coal tar pitch and calcium sulfate were mixed at a mass ratio of 93.5:5:2, and the other steps were carried out in the same manner as in Example 5 to obtain Battery A6. S content N in the S-containing conductive layer 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 9.4% by mass. 2 It is 0.30 mass %.

[0258] In Comparative Example 3, calcium sulfate was not added, and the composite particles and coal tar pitch were mixed at a mass ratio of 95:5. The other procedures were similar to those of Example 5, thereby obtaining Battery B3.

[0259] (Example 7)

[0260] In the preparation of the non-aqueous electrolyte, 1-propenyl-1,3-sultone (PRES) was added to a mixed solvent containing EC and DEC at a volume ratio of 3:7 at a concentration of 1 mass %, and LiPF was further added at a concentration of 1.0 mol / L. 6 The S content N in the S-containing conductive layer is 0.0447 W / m 2 0.0347 W / m 2 0.02 ... 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 3.9 mass%. 2 It is 0.11%.

[0261] (Example 8)

[0262] In the preparation of the non-aqueous electrolyte, ethylene sulfide (ES) was added to a mixed solvent containing EC and DEC at a volume ratio of 3:7 to give a concentration of 1 mass %, and LiPF was further added to a mixture at a concentration of 1.0 mol / L. 6 The S content N in the S-containing conductive layer was 0.0447 W / m 2 0.0347 W / m 2 0.02 ... 1 The mass ratio N of S contained in the S-containing conductive layer to the silicon-containing material (the total of the composite particles and the S-containing conductive layer) is 3.9 mass%. 2 It is 0.11%.

[0263] [Cycle test]

[0264] <Charging>

[0265] The battery was charged at a constant current of 1 It (800 mA) until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 1 / 20 It (40 mA).

[0266] <Discharge>

[0267] The battery was discharged at a constant current of 1 It (800 mA) until the voltage reached 2.75 V.

[0268] The rest period between charging and discharging was set to 10 minutes.

[0269] The charging and discharging were performed at 25°C.

[0270] For each battery, the discharge capacity C1 of the 1st cycle and the discharge capacity C100 of the 100th cycle were calculated. The ratio represented by (C1-C100) / C1 was evaluated as the capacity degradation rate R. Table 1 shows the evaluation results of the capacity degradation rate R of batteries A1 to A4, B1 and B2. Table 2 shows the evaluation results of the capacity degradation rate R of batteries A5 to A8 and B3. In Table 1, the value of the capacity degradation rate R obtained in the battery B1 of Comparative Example 1 is taken as 100, and the R value of each battery is expressed as a relative value. In Table 2, the value of the capacity degradation rate R obtained in the battery B3 of Comparative Example 3 is taken as 100, and the R value of each battery is expressed as a relative value. The smaller the R value, the smaller the reduction in the charge and discharge cycle characteristics, and the better.

[0271] [Table 1]

[0272]

[0273] [Table 2]

[0274]

[0275] Batteries A1 to A4, B1 and B2 use composite particles with a silicate phase as an ion-conducting phase as the negative electrode active material. In batteries A1 to A4, in which the surface of the composite particles is covered with a S-containing conductive layer and the S content of the S-containing conductive layer is set to 50% by mass or less relative to the entire conductive layer, a low capacity degradation rate can be obtained compared to batteries B1 and B2. This can be considered to be because, by making the S-containing conductive layer contain S, a film (solid electrolyte film) containing S is formed in a manner that covers the surface of the silicon-containing material, acting as a barrier layer to suppress side reactions, thereby suppressing the degradation of the silicate phase.

[0276] On the other hand, in Battery B2, although the surfaces of the composite particles were covered with the S-containing conductive layer, the S content of the S-containing conductive layer was greater than 50 mass % relative to the entire conductive layer, and thus the capacity degradation rate was considered to be higher than that of Battery B1.

[0277] In batteries A5 to A8 and B3, composite particles having an amorphous carbon phase as an ion-conducting phase were used as the negative electrode active material. In this case, as in the case of using a silicate phase as the ion-conducting phase, batteries A5 to A8 in which the surface of the composite particles was covered with a S-containing conductive layer and the S content of the S-containing conductive layer was set to 50% by mass or less relative to the entire conductive layer, were able to obtain a lower capacity degradation rate than battery B3.

[0278] Industrial Applicability

[0279] The secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0280] The present invention has been described with respect to the presently preferred embodiments, but such disclosure is not to be construed as limiting. Various modifications and changes should be apparent to those skilled in the art in the technical field to which the present invention belongs by reading the above disclosure. Therefore, the appended claims should be construed as including all modifications and changes without departing from the spirit and scope of the present invention.

[0281] Description of Reference Numerals

[0282] 1: electrode group, 2: positive electrode lead, 3: negative electrode lead, 4: battery case, 5: sealing plate, 6: negative electrode terminal, 7: gasket, 8: sealing plug, 11: composite particles, 12: silicate phase, 13 (16): silicon phase, 14: compound of element M, 15: S-containing conductive layer

Claims

1. A negative electrode material for a secondary battery, comprising a silicon-containing material, wherein the silicon-containing material comprises composite particles containing silicon and a conductive layer disposed on the surface of the composite particles, The composite particles include an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase, The conductive layer contains a sulfur component, and a content N1 of sulfur element in the conductive layer is 50 mass % or less.

2. The negative electrode material for a secondary battery according to claim 1, wherein A ratio N2 of the mass of sulfur element contained in the conductive layer to the mass of the silicon-containing material is greater than or equal to 0.02%.

3. The negative electrode material for a secondary battery according to claim 2, wherein: The ratio N2 is greater than or equal to 0.02% and less than or equal to 1%.

4. The negative electrode material for a secondary battery according to any one of claims 1 to 3, wherein The ion-conducting phase is a silicate phase.

5. The negative electrode material for a secondary battery according to claim 4, wherein The silicate phase includes at least one element selected from the group consisting of alkali metal elements and Group II elements.

6. The negative electrode material for a secondary battery according to claim 4, wherein The silicate phase further comprises an element M, The element M includes at least one selected from the group consisting of boron (B), aluminum (Al), zirconium (Zr), niobium (Nb), tantalum (Ta), vanadium (V), lanthanum (La), yttrium (Y), titanium (Ti), phosphorus (P), bismuth (Bi), zinc (Zn), tin (Sn), lead (Pb), antimony (Sb), cobalt (Co), erbium (Er), fluorine (F) and tungsten (W).

7. The negative electrode material for a secondary battery according to any one of claims 1 to 3, wherein The ion-conducting phase is an amorphous carbon phase.

8. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, The negative electrode includes a carbon material and the negative electrode material for a secondary battery according to any one of claims 1 to 3.

9. The secondary battery according to claim 8, wherein A ratio B / A of a mass B of the silicon-containing material to a mass A of the carbon material satisfies 0.05≤B / A≤0.

3.

10. The secondary battery according to claim 8, wherein The electrolyte does not contain a sulfur compound, or the electrolyte contains a sulfur compound at a concentration of 5 mass % or less.

Citation Information

Patent Citations

  • Semiconductor device, its manufacturing method and semiconductor manufacturing system

    JP2020537335A

  • Negative electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery

    WO2016035290A1

Cited By

  • Anode for lithium secondary battery and lithium secondary battery

    EP4811440A1